Nutrient Management, Energy Input–Output, and Economic Analyses of Eggplant Production Under Subtropical Conditions. Issue 4 (3rd July 2016) - Batabyal, Kaushik; Mandal, Biswapati; Hazra, Gora Chand
ABSTRACT: Energy input–output and cost analyses of production contribute to cost-effective management of input resources to improve productivity and profitability. The input–output energy balance and economics of eggplant ( Solanum melongena L.) production under 15 nutrient management (NM) practices, which included a control (normal farmer's production practice), organic (cow manure, vermicompost, or mustard oil cake), inorganic fertilization (recommended NPK at 100N–22P–42K kg·ha −1 and 150% of recommended NPK), and selected combinations, were analyzed. A complete account of energy inputs consumed, energy output produced, cost of production, and gross return was determined under each NM technology and these data were used to calculate energy efficiency and profitability. On average, fertilizer application ranked first in energy consumption (13.80 GJ·ha −1 ); the least energy (0.71 GJ·ha −1 ) was required for transplanting seedlings. Integrated NM technologies were more energy efficient, and more profitable, than inorganic and organic ones alone. For eggplant production 3 Mg·ha −1 vermicompost plus 150% of recommended NPK was the highest net energy gainer (110.5 GJ·ha −1 ) and most profitable with a maximum net return (INR 219, 343·ha −1 ; INR is Indian rupees, US$1 = 66 INR), highest benefit–cost ratio (3.4), and fairly high marginal rate of return (8.8). Organic technologies required less energy and were less profitable. Among organics, the highest energy-conserving efficiency and maximum profit were obtained with cow manure. Balanced fertilization with integrated sources of nutrients is the most energy-efficient management option for productive and profitable eggplant production under subtropical conditions.